2005
DOI: 10.1007/s00467-005-1956-z
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase, total antioxidant response, and peroxide levels in children with steroid-sensitive nephrotic syndrome

Abstract: Reactive oxygen species (ROS) are reported to play a role in inducing the proteinuria of nephrotic syndrome (NS). This study investigated paraoxonase (PON), total antioxidant response (TAR), and oxidant total peroxide together with serum proteins and lipoproteins in children with steroid-sensitive NS. The study included 40 children with steroid-sensitive NS (21 with acute-period NS in group I, 19 nonproteinuric while receiving steroids in group II) and 22 sex- and age-matched formerly nephrotic children in rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
1
27
2
Order By: Relevance
“…The most likely explanation for the lack of significant associations between leptin and BMI and between leptin and oxidant/ antioxidant parameters in our marasmic group may be the presence of a threshold beyond which leptin can not decrease physiologically, since excessive loss of adipose tissue is the main characteristics of marasmus. In previous studies, leptin was reported to be positively correlated with oxidant markers in children with nephrotic syndrome or chronic renal failure (33,34). In those studies elevated leptin levels had been found to be related to increased oxidative stress.…”
Section: Discussionmentioning
confidence: 90%
“…The most likely explanation for the lack of significant associations between leptin and BMI and between leptin and oxidant/ antioxidant parameters in our marasmic group may be the presence of a threshold beyond which leptin can not decrease physiologically, since excessive loss of adipose tissue is the main characteristics of marasmus. In previous studies, leptin was reported to be positively correlated with oxidant markers in children with nephrotic syndrome or chronic renal failure (33,34). In those studies elevated leptin levels had been found to be related to increased oxidative stress.…”
Section: Discussionmentioning
confidence: 90%
“…However, the study of Kawamura et al (48) suggested that glucocorticoids may have a therapeutic role through the stimulation/augmentation of the activity of antioxidant enzymes. In addition, the study of Ece et al (1) observed that steroid treatment did not suppress oxidative stress in SSNS.…”
Section: Serum Levels Of Total Cholesterol (Tc) Low-density Lipoprmentioning
confidence: 98%
“…M inimal change nephrotic syndrome (MCNS) is the most common form of nephrotic syndrome (NS) in children and generally responds well to treatment with prednisone (1). An important advance in understanding the pathogenesis of NS was the observation that oxygen-free radicals are possible mediators of injury in experimental nephrosis in rats.…”
mentioning
confidence: 99%
“…Of these, the majority were excluded after the first screening in terms of abstracts or titles, mainly because they were not relevant to INS. After full-text review of 14 articles, six [18][19][20][21][22][23] studies were excluded because they did not display the status of MDA, vitamin C or E. Finally, eight studies were included.…”
Section: Literature Searchmentioning
confidence: 99%